(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A design of Compact Bandpass Microstrip Filter is proposed for wireless communication applications like Bluetooth, Wi-Fi, and 5G. Filter is constructed using parallel-coupled Microstrip lines to form 5th order filter of an inverted C structure. Ground slotted technique is used to enhance the bandwidth with dielectric constant of 9.9. The designed filter is simulated at a center frequency of 5.87GHz and bandwidth of 1.9GHz with an insertion loss of -0.5dB, return loss of greater than 12dB. The proposed filter has a compact size, good increased bandwidth and cost-effective. These results are verified with the theoretically designed values and good agreements are recorded. Hence the proposed compact filter will provide a platform for designing and development of compact filters for the microwave regime.